1996
DOI: 10.3109/00365549609037978
|View full text |Cite
|
Sign up to set email alerts
|

High Incidence of Toxoplasmosis During Pregnancy in Nigeria

Abstract: Sera from 606 women of child-bearing age from the Benue River Basin area of Nigeria were screened by serological tests to determine the incidence of toxoplasmosis in Nigeria; 43.7% had serologic evidence of infection, increasing from 25% in the group of 15 to 18-year-old women to 71.4% in the 39-42 year age group. Using a previously published epidemiological model, the incidence rate for each age group varied from 0.5% for 15 years old women to 5.3% in the age group 37 years, with an overall rate of 1.8%. Exte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
2

Year Published

2005
2005
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 7 publications
0
12
0
2
Order By: Relevance
“…Cuba, for example, has 29.1% seronegativity in pregnant women 20 . However such data differ between authors, in Nigeria, women of reproductive age show 54.3% seronegativity 34 . The existence of this group of women susceptible to first infection during pregnancy and possible congenital transmission indicates the need for primary, secondary and tertiary prevention.…”
Section: ) (X Rodent) + (51) (X Cat) + (91) (X Soil) + (43)mentioning
confidence: 74%
“…Cuba, for example, has 29.1% seronegativity in pregnant women 20 . However such data differ between authors, in Nigeria, women of reproductive age show 54.3% seronegativity 34 . The existence of this group of women susceptible to first infection during pregnancy and possible congenital transmission indicates the need for primary, secondary and tertiary prevention.…”
Section: ) (X Rodent) + (51) (X Cat) + (91) (X Soil) + (43)mentioning
confidence: 74%
“…Recent seroepidemiological surveys performed in different segments of the Brazilian population revealed infection rates ranging from 32.4 to 74.5%, depending on the age, with highest values occurring in adults 3,16,17,18 . In other countries high rates of human infection with T. gondii can also be found 1,6,8,11,15 .…”
Section: Discussionmentioning
confidence: 99%
“…In a similar study in Nigeria, seroprevalence rates of toxoplasmosis were estimated to vary from 7% - 51.3% in normal pregnant women to 17.5% - 52.3% in women with abnormal pregnancies and abortions (6, 7). Conducted studies in Senegal and Sudan in pregnant women showed IgG seroprevalence rates of 40.2% and 34.1% (8, 9).…”
Section: Introductionmentioning
confidence: 95%